Analysis of Sika Cim Additive Material Proportion In Beam-Column Joint for Fabricated House - Anggit Mas Arifudin; Setya Winarno (Universitas Medan Area, 2023)
The design compressive strength (fâ€™c) is 21,7 Mpa / K250 and the chemical liquid was used is Sika Cim.Â Variation of Sika Cim adding that used is 0%; 0,3%; 0,5%; 0,8%; 1%; and 1,2% toward the weight of cement used. The each variation consists of 3 sample with 2 sample that will be at compressive strength tested at the age of 7 days, and 2 sample for compressive strength control that tested at the age of 28 days. From these all variations of Sika Cim adding, the optimum point for connection material can be founded and then it will used to fabricated house panel assembling which analise damage model of the connection. Then calculating the cost that used to make connection with the optimum Sika Cim adding, and then compare it with the cost of normal concrete with same quality. From this study can be founded that level of optimum Sika Cim is 2263,54 ml or 0,52% from the cement which used for 1 m3 volume of the concrete.. Level of Sika can increase 11,8 MPa of compressive strength or 58,38% from the normal concrete without Sika Cim. Sika Cim using at K200 concrete to produce K250 concrete is 1182,219 ml/m3, with 7,48% cost from total cost for each K200 readymix concrete. This Sika Cim adding can economize the cost for about Rp. 51.397,67 for each m3 concrete. The composition of the mixture with the optimum Sika Cim applied to the precast column beam connection material, produces a joint that has a good crack pattern.